Development and Validation of a Mathematical Model for Predicting the Performance of Rotary Hammer Drills - (:unkn) unknown (My University, 2013)
Rotary hammer drills are specialized drills used by plumbers, electricians, and other construction trades to drill holes in concrete. This type of tool employs a mechanism driven by an electric motor to compress a column of air, generating an impact on a drill bit to break the concrete work piece. Rotary hammer development requires the ability to accurately predict tool performance to minimize the number of prototype iterations required during the design phase and ensure the tool delivers a satisfactory level of performance. In order to predict the performance of a rotary hammer drill, a mathematical model was developed to simulate the response of the tool under load, from the time the tool is activated until it achieves steady state. Inputs for this model were taken from physical tool dimensions, motor performance data, and FEA simulation of component impact events. Validation of the model was carried out by simulating the performance of a Milwaukee Electric Tool model 5262-20 rotary hammer and comparing the model outputs to actual performance data, measured following the European Power Tool Association test procedure 05/2009 - Measurement of single impact energy of rotary hammers and breakers.